Magic Pickle and the planet of the grapes - Morse, Scott (New York Scholastic, 2008)
Meet flying superhero Magic Pickle, a secret weapon developed in a secret military lab---under little JoJo Wigwam's bedroom floor. Together Magic Pickle and Jo-Jo, afeisty eight-year-old, go after Ray Sin, a renegade raisin from the Brotherhood of Evil Produce. Ray Sin has a dastardly plan: to turn every human being on the planet into big, juicy, mindless grapes, so he can rule the world!
Q
680
Accelerated Reader AR
Reading Counts RC
Keywords: Pickles -- Juvenile fiction; Pickles -- Fiction; Canning and preserving -- Juvenile fiction; Grapes -- Juvenile fiction; Vegetables -- Juvenile fiction; Pickles -- Fiction; Grapes -- Fiction; Vegetables -- Fiction; Canning and preserving -- Fiction; Comic books, strips, etc